Sejarah Perkembangan dan Kemunduran Sastra Arab Mahjar di Australia Oleh Para Sastrawan Arab - Surahman, Nashrulloh (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
This research is a study of the history of the development and decline of Mahjar or Diaspora Arabic literature in Australia. Countries in Europe and America have become countries where Arabs have immigrated after World War II. Mahjar Arabic literature is the result of acculturation between two cultures (East-West) and even multicultural acculturation which is supported by the spiritual strength and imagination of diaspora writers. History has recorded that Arabs who immigrated or moved to Diaspora countries have made such great works. This means that the history of diaspora literature needs to be studied in more depth. In this article, the author wants to write a history of Mahjar Arabic literature in Australia, because there is still a lack of writing about Mahjar Arabic literature in this country. From the results of research conducted by the author, it is clear that the role of Arab writers is very important in the development and decline of Mahjar Arabic literature in Australia. The large number of writings in the form of media, journalists and even literary works by Arab writers has also become one of the factors in the development of Arab major/diaspora literature in Australia. On the other hand, the lack of financial resources and the lack of strong and influential Arab institutional organizations are factors in the decline of diaspora literature.